Accuracy of the over-preparation technique in implant surgery in the maxillary anterior region: an in vitro study - Luming Wei; Xuzhe Zha; Jianhua Ji; Changyong Yuan; Huiying Guo; Penglai Wang (BMC Oral Health)
Abstract Background In the maxillary anterior region, differences in bone density along the drilling path can impact the accuracy of implant placement despite the use of a surgical guide. Hence, the aim of this in vitro study was to investigate the accuracy of implant placement using the over-preparation technique in different drilling environments in the maxillary anterior region. Methods Three experimental models (a, b, and c) were designed and fabricated to simulate the following drilling environments (n = 60 each): unhealed bone, less dense bone, and dense bone after tooth extraction. The models were subjected to implant cavity preparation and placement using the over-preparation technique (group OPT) and conventional surgical guide technique (group CGT). Differences between the actual positions and the planned positions of the implants were calculated. Results The deviations of the implants in the group OPT in Model a and Model b were significantly smaller than those in the group CGT (P < 0.05). Among the group OPT, Model c presented with the smallest deviation, followed by Model b and Model a (P < 0.05), and the CGT group showed the same trend. Conclusions In the maxillary anterior region, differences in bone density along the drilling path can adversely affect the accuracy of implant placement. These discrepancies can be significantly minimized using the over-preparation technique.